Exploring women’s leadership success in inclusive leadership in Islamic higher education: integrating Big Five personality and Islamic values - Ghafar, Muhammad; Imtihanah, Anis Hidayatul; Shiddiq, Jamaluddin; Wilujeng, Hestu; Hamidah, Noor Zinatul (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study integrates the dimensions of the Big Five personality traits with an Islamic perspective (Shiddiq or truthfulness; Amanah or trustworthiness; Tabligh or conveying; and Fathonah or wisdom) to explore the success of women’s leadership. The main problem underlying this study is the lack of understanding of the influence of Islamic values on personality characteristics that support the success of women’s leadership in Islamic higher education (IHE) through an inclusive leadership approach. The relevance of this study lies in the importance of identifying personality factors and religious values that can improve the effectiveness of women’s leadership in Islamic educational environments. Quantitative research using a survey method with partial least squares-structural equation modelling (PLS-SEM) analysis on 111 respondents consisting of stakeholders in three IHEs in Indonesia using structured questionnaires as a data collection technique. The main findings indicate that Islamic values, such as Shiddiq and Amanah have a significant positive influence on personality characteristics such as conscientiousness (CON) and agreeableness (AGR), which have a direct impact on the success of women’s inclusive leadership. The conclusion of this study underscores the importance of leadership training programs that focus on the integration of Islamic values and personality characteristics to strengthen women's inclusive leadership skills.